PORTFOLIO AS AN AUTHENTIC ASSESSMENT INSTRUMENT IN WRITING INSTRUCTION: A LITERATURE REVIEW STUDY - suwarti, indri (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to examine the use of portfolio as an authentic assessment instrument in learning to write Indonesian. Through a literature review approach to twenty-five scientific articles, this study focuses on three main aspects: (1) the basic concepts and working principles of portfolio assessment, (2) the effectiveness of portfolios in improving students' writing skills, and (3) obstacles and strategies for their implementation in the classroom. The results of the study show that portfolio assessment emphasizes process-based assessments that are formative and summative, authentic, reflective, and student-centered. The portfolio has been proven to be effective in improving the quality of writing, critical thinking skills, learning motivation, and metacognitive awareness of students. However, its implementation still faces a number of challenges such as limited time, administrative burden on teachers, low understanding of concepts, and limited infrastructure. Various strategies, such as the use of e-portfolios, teacher training, and the development of contextual rubrics are recommended to optimize their implementation. These findings confirm that portfolio assessment is in line with the spirit of the Independent Curriculum and can be an alternative to comprehensive, humane, and transformative assessments in writing learning.